Intelligent virtual agents 10th International Conference, IVA 2011, Reykjavik, Iceland, September 15-17, 2011. Proceedings - Hannes Hogni Vilhjalmsson; Kopp, Stefan; Marsella, Stacy; Thorisson, Kristinn R. (Lecture notes in artificial intelligence, 2011)
This book constitutes the refereed proceedings of the 11th International Conference on Intelligent Virtual Agents, IVA 2011, held in Reykjavik, Island, in September 2011. The 18 revised full papers and 27 revised short papers presented together with 25 poster papers were carefully reviewed and selected from 91 submissions. The papers are organized in topical sections on social and dramatic interaction; guides and relational agents; nonverbal behavior; adaptation and coordination; listening and feedback; frameworks and tools; cooperation and copresence; emotion; poster abstracts.